The Role of Optic Flow and Gaze Direction on Postural Control - Milena Raffi; Michela Persiani; Alessandro Piras (Emerging Science Journal, 2022)
Objective: The observers use the optic flow to control self-motion. However, the current state of knowledge indicates that it is difficult to understand how optic flow is used by the visual system without a direct measurement of the changes in the flow patterns caused by eye movements during natural behaviour. The purpose of this literature review is to highlight the importance of the integration between optic flow and eye movements for postural control. Methods: A literature review of the electronic papers through July 2022 was independently performed by three investigators. The selection of the studies was made by a search on PubMed, Scopus, and Google Scholar with two groups of selected keywords. We excluded papers performed on subjects with pathologies, children, and the elderly. Results: The results of this literature analysis highlight that eye movements are required to drive visual motion processing and heading perception in both static and dynamic contexts. Conclusion: Although we now know many neural mechanisms that process heading direction from the optic flow field, a consideration of optic flow patterns relative to gaze direction provides more detailed information on how the retinal flow field is used to control body balance. Doi: 10.28991/ESJ-2022-06-06-020 Full Text: PDF